Security, privacy, and governance : protecting data, and using data to protect systems (O'Reilly Media, 2015)
"Fraud and abuse aimed at organizations big and small is becoming more and more sophisticated. In this unique O'Reilly video collection--taken from live sessions at Strata + Hadoop World 2015 in San Jose, California--you'll learn about security tools and techniques for dealing with this growing and ever-present threat."--Resource description page.